The potential, variety, and nutrient content of natural vegetation as feedstuffs grown under cashewnut plantation - E Sutedi; I-W Mathius; NIP Suratmini; S. Oloan ButarButar; T Manurung; S Yuhaeni; Tanda S. Panjaitan; A Muzaini (Jurnal Ilmu Ternak dan Veteriner, 2001)
Ruminant production is limited by the quality, the sufficiency and the continuation of feed supply, especially during the dry season. The objective of the study was to find out the potency, type and quality of natural vegetation grown under cashewnut plantation. The study was carried out by exploration of existing natural vegetation resources in cashewnut plantation area. Results showed that native pasture growing under cashewnut plantation area comprised of dry-tolerant grasses and legumes, such as Setaria sp., Themeda sp., Calopogonium mucunoides, and Desmodium sp. The fresh yield and the dry matter production of natural vegetation grown under less than eight years old of cashewnut plantation was lower compared to those grown under cashewnut plantation of more than eight years old. This may be due to shading by the tree crop, which is known to reduce the photosynthetically active radiation reaching the ground of vegetation. It seems that, light is the critical factor affecting the growth of vegetation underneath tree canopies. Carrying capacity of native forages grown under cashewnut plantation was only 0.5 animal unit of ruminant/ha/year.   Key words: Natural vegetation, cashewnut plantation, carrying capacity